Matching students' learning styles and lecturers' teaching styles / Malina Hanum Mohd Kamal - Mohd Kamal, Malina Hanum (2012)
Teaching and learning is best known as one of the progressions by which the society deliberately conveys its accumulated information and knowledge, skills and values from one generation to another. In other words, it is a process by which people learn formally while involving in the development of instruction, teaching and learning from any type of educational institutions including primary, secondary and tertiary education. As for graduates, the tertiary education or best known as higher education that being offered in higher learning institution is the best option for them to raise a higher degree of essential attributes as a students. Aripin and Mahmood (2008) further suggested that institutions of higher learning are engaged in a sustained and continuous process of maximizing the quality of their graduates so as to enhance their readiness for the job market. Thus, it is important for educational institutions to focus on improving critical aspects of teaching and learning.